THU0535 Significantly Better Patient-Reported Outcomes in Women with Early Inflammatory Arthritis Using Oral Contraceptives Compared to Never Users. (23rd January 2014) - Westhoff, G.; Callhoff, J.; Schett, G.; Zink, A.
Abstract : Background: Data on the effects of oral contraceptives (OC) on the course of inflammatory arthritis (IA) are controversial. While some observations suggested a beneficial effect on disease activity, others did not. However, a recent analysis of data from the Norfolk Arthritis Register (NOAR) showed that the use of OC at symptom onset, and even years before, is associated with beneficial functional outcomes. Objectives: To investigate the association between the use of OC and arthritis outcomes in women with early IA within the first 12 months of rheumatologic care. Methods: 311 women with early IA (<6 months), who were 18 - 55 years old and did not use hormone replacement therapy, were followed with respect to acute phase reactants (CRP, ESR), swollen and tender joint counts (S/TJC28), duration of morning stiffness and physician-reported global health (GH 0-10), as well as to the patient-reported dimensions pain, morning stiffness, fatigue, global health (VAS 0-10), functional capacity (FFbH 0-100), and the sum score of the Patient Health Questionnaire Depression Measurement (PHQ9, 0-27). The use of OC was reported as never, past or currently. Outcomes were adjusted for age, body mass index (BMI), number of children and years of education by generalized linear models. Results: Women were 44 ±9 years old and had symptom duration of 12 ±7 weeks at study entry. At baseline, 61% fulfilled the new RA classification criteria and 82% were clinically diagnosed with RA at 12 months. 85% took DMARDs at that point in time. 22% had never used OC (mean age 45), 57% had used them in the past (mean age 47) and 21% used them currently (mean age 35 years). The mean intake lasted 14 ±8 years in past and 16 ±8 years in current users. The current use of OC was at no time associated with acute phase reactants, joint counts, duration of morning stiffness or antirheumatic therapies. It was, however, significantly associated with almost all considered patient-reported outcomes (PROs) (Table ). The effect of OC on PROs was, notably, almost the same in past and current users, although the past users were older and might not have used OC for several years before arthritis onset. Conclusions: Our findings are in accordance with former observations that the use of OC has a beneficial effect on IA symptoms. They confirm the NOAR data that women with past or current OC use have better functional outcomes without having less signs of inflammation. Our data suggest that the 'stimulating hormone estrogen' may affect catabolic or anabolic bioenergetic processes, resulting in less fatigue, and a better function in daily life, without affecting inflammation itself. The long-lasting effect of previous OC use needs to be explained. The use of hormones should be routinely reported in studies observing inflammatory arthritis. Disclosure of Interest: None Declared